Pelatihan Pengenalan Autocad 2D Bagi Siswa Di SMA Kesatrian 2 Yayasan Pendidikan Kesatrian Semarang - Seno Suharyo; Trias Widorini; Wardana Galih Pamungkas (Jurnal Pengabdian KOLABORATIF, 2023)
The rapid development of technology today makes people adapt. In the field of education, especially in the field of engineering drawing design, several computer programs have been very helpful in completing work with good results. Human resources are needed who are willing to learn and able to adapt to technological advances so that they can run computer programs optimally. For high school students who are interested in continuing their education in engineering at the university, skills in using computer programs will be very helpful. Therefore, the Civil Engineering Department, Faculty of Engineering, University of Semarang carries out community service, especially for students of SMA Kesatrian 2 Semarang, namely "Training for Introduction of 2D AutoCAD for Students at SMA Kesatrian 2, Semarang Kesatrian Education Foundation". This training is carried out to provide an introduction to skills in technical drawing with computer programs for high school students so that they can complement the knowledge learned at school. The method used is to do tutorials and practice directly in the Planning Laboratory of the Civil Engineering Department, Faculty of Engineering, University of Semarang. The number of participants in this activity was 25 students. The activity was carried out on August 19, 2019, at the Planning Laboratory of the USM Faculty of Engineering. The students are mostly able to follow the theory and exercises given in this training module.